Back end support for information retrieval of trajectory dataset: Case study: Iceberg movements in antarctica - Iswari, L.; Turdukulov, Ulanbek; Morales, J. (2010)
Trajectory is defined as a movement of an object in space and time, which consists of a set of spatial and temporal data. Exploration of this dataset can be used to extract the movement behaviour of moving objects that is previously unknown. This research proposes several alternatives on how to retrieve information from trajectory dataset in a database system with the Antarctic's iceberg movements as a case study. There are two types of back end support are implemented, i.e. for data preprocessing and data extraction. Data pre-processing deals with managing data at the initial stage of data storage, update and consistency check. Data extraction deals with information that can be retrieved from trajectory, i.e. the geometric properties, such as lifespan, average speed, and moving direction, and the specific need of application, such as iceberg event detection. © 2010 IEEE.